Perforation drilling for easing spudcan–footprint interaction issues. (1st February 2016) - Hossain, M.S.; Stainforth, R.
Abstract: The interaction between a spudcan and an existing footprint is a major concern during jack-up rig installation. No guidelines were provided in the recently finalised version of ISO guidelines 19905-1 in regards to mitigating spudcan–footprint interaction issues except some proposed considerations due to scarce of detailed investigation. This paper reports a measure for easing spudcan–footprint interaction issues, with the efficiency of perforation drilling tested through model tests carried out at 1 g. The soil conditions tested simulate soft seabed strength profiles close to the mudline, varying the undrained shear strength. The most critical reinstallation locations of 0.5 D and 1 D ( D =spudcan diameter) and existing footprint depth of 0.33 D were investigated. The removal of soil (through perforation) inside the spudcan perimeter, with an area of 9% perforated, reduced the induced maximum moment, horizontal force, and horizontal sliding distance by up to 80%, 83%, and 76% respectively. Highlights: The efficiency of perforation drilling in easing footprint issues was tested The soil conditions tested simulate soft seabed strength profiles Critical locations of spudcan installation related to the footprint were examined Perforation drilling reduced moment, horizontal force, and sliding distance Potential of using perforation drilling in easing footprint issues was confirmed